Pre-service teachers’ disposition and attitude to environmental literacy in sanitation and waste management in a Nigerian university - Ogunyemi, Biodun; Ifegbesan, Ayodeji P. (Journal of Education in Black Sea Region, 2022)
Environmentally literate teachers are indispensable to sustainably addressing the challenge of poor sanitation and waste mismanagement in less-industrialized countries. In Nigeria, efforts at stemming the trends of urban waste management problems through stringent environmental regulations of the military in the 1980s have since yielded ways to programs of information, communication and education embedded in environmental education under current civilian dispensation. This study analyzed attitudes and dispositions of 125 graduating pre-service teachers, drawn from a Nigerian public university, towards environmental sanitation and waste management within the context of environmental literacy (EL). The student-teachers were aware of the adverse effects of unsanitary practices. However, they had not embraced environmental sanitation practices as part of daily routines or a way of life. While gender and age were not found to be significantly related to pre-service teachers’ EL knowledge and attitude, subject specialization correlated with knowledge just as family background did with attitude. The study concluded that the current information-sharing approach is not enough to actualize the action-oriented nature of EL and calls for curricular review to infuse environmental education (EE) concepts, activities, and methods for addressing the existing gaps in teacher education programs in Nigeria.